2003
DOI: 10.1046/j.1365-2036.2003.01679.x
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary understanding and management of reflux and constipation in the general population and pregnancy: a consensus meeting

Abstract: Summary Background : Gastro‐oesophageal reflux disease (GERD) and constipation have a major impact on public health; however, the wide variety of treatment options presents difficulties for recommending therapy. Lack of definitive guidelines in pharmacy and general practice medicine further exacerbates the decision dilemma. Aims : To address these issues, a panel of experts discussed the principles and practice of treating GERD and constipation in the general population and in pregnancy, with the aim of develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0
10

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 57 publications
0
77
0
10
Order By: Relevance
“…There is the well-understood caution in withholding of drugs from pregnant women. The recommended strategy to treat GERD during pregnancy indeed is a step-up approach [34]. Antacids are considered first-line drugs, especially if symptoms are not severe.…”
Section: Discussionmentioning
confidence: 99%
“…There is the well-understood caution in withholding of drugs from pregnant women. The recommended strategy to treat GERD during pregnancy indeed is a step-up approach [34]. Antacids are considered first-line drugs, especially if symptoms are not severe.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of these discussions was to update a consensus and opinion-based treatment algorithm developed at an earlier meeting in 2002. 13 Several of the experts gave presentations concerning various aspects of GERD, focusing on current knowledge and clinical practice. This paper presents a summary of the discussions that enabled the panel to update the Gstaad Treatment Guidelines 13 for reflux disorders by reaching a consensus on a practical treatment algorithm for GERD.…”
Section: Introductionmentioning
confidence: 99%
“…In a European consensus meeting conducted in 2003 (Contemporary understanding and management of reflux and constipation in the general population and pregnancy: a consensus meeting), it was reported that the use of calcium-based antacids in pregnant women with GERD could be beneficial because it reduced the risk of hypertension and preeclampsia (8). Moreover, in a comprehensive randomized placebo-controlled study, it was demonstrated that the use of magnesium sulfate during pregnancy reduced eclampsia and maternal risk; it also caused no serious side effects in the short term.…”
Section: Antacidsmentioning
confidence: 99%